2008
DOI: 10.1111/j.1469-8137.2008.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic redistribution of water from Pinus ponderosa trees to seedlings: evidence for an ectomycorrhizal pathway

Abstract: Summary• While there is strong evidence for hydraulic redistribution (HR) of soil water by trees, it is not known if common mycorrhizal networks (CMN) can facilitate HR from mature trees to seedlings under field conditions.• Ponderosa pine (Pinus ponderosa) seedlings were planted into root-excluding 61-µm mesh barrier chambers buried in an old-growth pine forest. After 2 yr, several mature trees were cut and water enriched in D 2 O and acid fuchsin dye was applied to the stumps.• Fine roots and mycorrhizal roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 48 publications
(76 reference statements)
2
75
0
Order By: Relevance
“…In this regard, EM and AM fungi may differ significantly. Unlike AM, EM fungi are capable of forming relatively largediameter rhizomorphs made of fused hyphae where hydraulic conductance is high enough to contribute significant water to plants (Brownlee et al, 1983;Warren et al, 2008). Of course, these larger hyphae may be unable to access the finest matrix pores.…”
Section: Hypothesis 8 Mycorrhizal Fungi Can Use Matrixmentioning
confidence: 99%
“…In this regard, EM and AM fungi may differ significantly. Unlike AM, EM fungi are capable of forming relatively largediameter rhizomorphs made of fused hyphae where hydraulic conductance is high enough to contribute significant water to plants (Brownlee et al, 1983;Warren et al, 2008). Of course, these larger hyphae may be unable to access the finest matrix pores.…”
Section: Hypothesis 8 Mycorrhizal Fungi Can Use Matrixmentioning
confidence: 99%
“…Recently, an experiment using deuterium labelled water presented strong evidence for hydraulic redistribution of soil water by a common mycorrhizal network from mature trees to seedlings under field conditions (Warren et al 2008).…”
mentioning
confidence: 99%
“…I note that in this study grasses have access to water hydraulically lifted by woody plants, as shown by a number of other authors Zou et al, 2005;Scott et al, 2008) and in contrast to other studies suggesting that the hydraulically lifted water may remain confined to microsites within the soil profile close to the roots that have performed hydraulic lift (Brooks et al, 2006). Recent studies indicate that grasses may take up lifted water through ecto-and endomycorrhizal networks (CMNs) (Egerton-Warburton et al, 2007;Warren et al, 2008). Past studies suggested that HL plays an important role in the facilitation of woody plants on grasses (Riginos et al, 2009;Moustakas et al, 2013;Dohn et al, 2013).…”
Section: Case Study: Kalahari Transect In Southern Africamentioning
confidence: 44%
“…The benefits gained by shallow-rooted plants in scavenging lifted water have been documented in experimental studies (Richards and Caldwell, 1987;Zou et al, 2005;Brooks et al, 2006). More recent studies indicate that shallow-rooted plants can directly take up lifted water through ecto-and endomycorrhizal networks (CMNs) (EgertonWarburton et al, 2007;Warren et al, 2008). However, the hydraulic lifter itself may be a strong competitor for lifted water and thus competition may dominate (Ludwig et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation